ANALISIS SISTEM PENGENDALIAN INTERN PEMERINTAH PADA PENGELOLAAN BELANJA BANTUAN SOSIAL DI DINAS SOSIAL KOTA PAREPARE - Nurwani, Nurwani (Economos : Jurnal Ekonomi dan Bisnis, 2018)
This research is entitled "Analysis of the Government Internal Control System in the Social Assistance Expenditures Management at the Social Service Office of the Parepare City". The problem raised in this study is the problem found in the 2015of Local Government Work Planof Parepare City, that there is no legitimate data about PMKS and the standardization of PMKS that receives assistance. The purpose of this study is to find out the implementation of the internal control system carried out by the Social Service Office in managing social assistance expenditure. The research method used in this study is quantitative data in the form of social assistance budget data for PMKS and qualitative data in the form of sentences through interviews. The results showed that of the 26 types of PMKS, only 5 PMKS received a budget and each year the social assistance budget increased from 2013-2016. Related to the government internal control system, there are elements that are not implemented well, namely control activities, exactly in the sub-elements of control over information system management, and accurate and timely sub-elements, and monitoring elements, exactly continuous monitoring sub-elements and separate evaluation sub-elements.